Ialodê Lélia Gonzalez e sua contribuição ao estudo das relações raciais brasileiras - Pereira, Evelyn Cristina Santana (2023)
This research explores the work of intellectual and activist Lélia Gonzalez, taking her as an unavoidable reference in the debate on racial relations, which in turn are fundamental to the theories that interpret Brazilian formation. In this area, Gonzalez elaborates on the places that black women occupy in society, without losing sight of the entire Brazilian population and the process of Africanization that gave rise to it. From this production, we are interested in highlighting two paths taken by the author: (1) the way in which Gonzalez presents the perspective of black women in the interpretative dispute over Brazilian cultural formation, which occurs in symbiosis with her pioneering spirit in structuring the black feminist movement, and ( 2) his approach to understanding a black Brazil, that is, a country that was organized not only under the efforts of men and women of African descent, but through and with their participation; for that purpose, Gonzalez created the categories Mulata, Pretuguês and Amefricanização, which seek to highlight this Amefrican matrix. Both do not end in deprivation, but show the protagonism of black men and women in the process of formation of Brazil. To carry out this research, we used the work of authors and authors used by Gonzalez in his reasoning, as well as contemporary researchers who are dedicated to researching his work. As Lélia, due to her training, activity and circulation, was committed to the use of art as a means of reflection, we sought to dialogue with artistic expressions that would help us to understand the author's production and the reality about which she discusses.